Reinventing the coexistence of multiculturalism in Hong Kong: the role of Kowloon Mosque - Chun-Leung Jacky Li; Mohd Roslan Mohd Nor; Khairul Anuwar Mustaffa; Khalid Isa (Cogent Arts & Humanities)
This paper seeks to explore the significance of Kowloon Mosque (or Masjid Kowloon) in demonstrating cultural coexistence within Hong Kong. In this cultural study, along with incorporating a sociological perspective, the aim is to explore the connections between Kowloon Mosque, the Muslim community, and Hong Kong residents. The intention behind this exploration is to establish a scientific basis that highlights the interdependence among these entities. To support this analysis, sources will be drawn from historical books, statistical publications, personal visits made within and around the mosque premises as well as empirical observations conducted in Hong Kong. This article seeks to demonstrate that coexistence culture can indeed thrive in reality by employing historical and textual analyses. Furthermore, it aims to shed light on the prerequisites necessary for fostering harmonious coexistence within society.